AUPHA and Globalization: A Perspective on the Future - Glandon, Gerald L. (Frontiers in Public Health, 2019)
The Association of University Programs in Health Administration (AUPHA) celebrated its 70th year in 2018 with a publication of a book on its history (Looking Back to Look Forward: AUPHA at 70) (1). As part of that reflection, we engaged in a fundamental reconsideration of our current and future leadership role in supporting healthcare management education. The consideration gets to the core of why any association exists and how does an association best serve the needs of its constituencies. The purpose is to determine what lessons AUPHA's evolution has for healthcare management education associations globally. This perspective will address three questions: 1) What is AUPHA and what is its role in the US healthcare system? 2) What is the value proposition for AUPHA? 3) What lessons learned does AUPHA have to share about the contribution of an association to global health management education?